PWE-234 Management and outcomes of intestinal failure in a district general hospital setting. (22nd June 2015) - Tamura, C; Kalaiselvan, R; Kenyon, A; Smith, D; Sarwar, N; Walsh, CJ
Abstract : Introduction: Centralisation of intestinal failure (IF) services is being considered. It will not be possible to manage all patients with type 2 IF in national centres and many patients will need to be managed regionally. We have audited our practice of type 2 and 3 IF with respect to aetiology, management and outcomes in a DGH setting. Method: Retrospective analysis of consecutive patients admitted with type 2/3 IF requiring parenteral nutrition (PN) for > 28 days between 01/09/2009–31/07/2014 was done from prospectively maintained database and cross-referenced with case notes (electronic and paper). Data are represented as median (range). Results: There were 84 patients (45 women) admitted during the study period. The median age was 68 (20–90) years. Aetiology: PN details: Patients were managed on PN for a median of 65 (29–728) days while being an in-patient. The catheter related infection rate was 0.16 CRBI /1000 catheter-days. PN was administered by peripherally inserted central catheters by a nurse led service. Outcome: Nutritional autonomy was achieved following conservative management in 17 (20%) patients. 46 (55%) underwent one-stage (n = 24) or two-stage (n = 22) surgical procedures and achieved nutritional autonomy. 8(10%) required home parenteral nutrition of which 6 were palliative patients who were discharged to hospice and 2 were referred to national IF centres. 12(14%) with type 2 IF and 1 (1%) with type 3 IF died in hospital. At a median follow-up of 479 (19–1885) days, 18 (21%) with type 2 IF and 6 (7%) with type 3 IF died. Conclusion: Sepsis management and safe PN administration is the key to managing patients with IF and can be done in regional units. Disclosure of interest: None Declared.